2013
DOI: 10.5546/aap.2013.eng.110
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of idiopathic hypercalciuria and its impact on associated diseases

Abstract: Idiopathic hypercalciuria may be associated with urinary tract infection, hematuria, nephrolithiasis and osteopenia. In order to describe the occurrence of these concurrent conditions related to the variation in urinary calcium and hypercalciuria response to sequential therapy, with a normal protein and low sodium diet, potassium citrate and hydrochlorothiazide; 46 patients older than 4 years, with no urinary tract diseases, sphincter control and normal blood creatinine values were followed-up during 43 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…O tratamento hoje preconizado para essa condição inclui ingestão hídrica abundante, reposição de citrato de potássio e diuréticos tiazídicos, além de dieta normocalcêmica e com restrição de sódio e de proteínas animais 18,[20][21][22] .…”
Section: Discussionunclassified
“…O tratamento hoje preconizado para essa condição inclui ingestão hídrica abundante, reposição de citrato de potássio e diuréticos tiazídicos, além de dieta normocalcêmica e com restrição de sódio e de proteínas animais 18,[20][21][22] .…”
Section: Discussionunclassified
“…In studies, the incidence of IH was determined as 28-35% in patients with microscopic or macroscopic haematuria (8,9). Although microscopic haematuria progresses asymptomatically in IH, there can sometimes be dysuria and suprapubic pain with (22), haematuria (43%) was the most common cause of admission. In our study, patients applied to hospital with abdominal pain and UTI and then haematuria as the third complaint.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research revealed increased destruction and reduced bone mass in patients with calcium urolithiasis. Some studies indicated that hypercalciuria and increased excretion of potassium, which are present in majority of urolithiasis patients, turned out to be major risk factors for osteoporosis and bone fracture in postmenopausal women (3)(4)(5)(6)(7). In their study, Denburg et al also concluded that urolithiasis is associated with high incidence of bone fracture, especially in women older than 70 (8).…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%